2023
DOI: 10.1021/acs.est.2c07793
|View full text |Cite
|
Sign up to set email alerts
|

Large Contribution of Nitrous Acid to Soil-Emitted Reactive Oxidized Nitrogen and Its Effect on Air Quality

Abstract: Soil emissions have long been recognized as an important source of nitric oxide (NO), which regulates atmospheric oxidative capacity and the production of air pollutants. Recent research has also indicated that nitrous acid (HONO) can be emitted in significant quantities from soil microbial activities. However, only a few studies have quantified emissions of HONO along with NO from a wide range of soil types. In this study, we measured emissions of HONO and NO from soil samples collected from 48 sites across C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 67 publications
2
12
0
Order By: Relevance
“…For example, Wang et al evaluated the impact of soil emissions on air quality in North China, finding that soil emissions contributed ∼17% of HONO, with this contribution reaching ∼50% during fertilization. 40,41 Although our sampling site is located in an urban area, it is surrounded by extensive cultivated land (Figure S9). The findings of this study and others highlight soil emission as an important source of HONO.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For example, Wang et al evaluated the impact of soil emissions on air quality in North China, finding that soil emissions contributed ∼17% of HONO, with this contribution reaching ∼50% during fertilization. 40,41 Although our sampling site is located in an urban area, it is surrounded by extensive cultivated land (Figure S9). The findings of this study and others highlight soil emission as an important source of HONO.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We find that assuming an uncertainty of 20% in GWETTOP and its representation of SWC in units of % leads to −12–19% and 4–22% differences in the estimated HONO soil emissions in 2017 over China and NCP compared to our base estimate, respectively. More measurement studies are required to provide better observational constraints on soil HONO emission parametrization in CTMs. , …”
Section: Methodsmentioning
confidence: 99%
“…More measurement studies are required to provide better observational constraints on soil HONO emission parametrization in CTMs. 21,31 Figure 2 presents the N r emissions from anthropogenic fuel combustion and soil emissions in June−July. We note that we do not include traffic HONO emissions due to the lack of available emission inventory, and also because the traffic HONO emissions are much smaller than those from soil and contribute negligibly to the daytime HONO except for central urban areas.…”
Section: Implementation Of Soil Hono Emissions In Geos-chemmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10][11][12][13][14][15][16] Microplastics, specifically, have been implicated as detrimental to the bladder epithelial cells of mice [17] and the gut health of zooplankton Daphnia magna. [18] Regarding the adverse effects of nanoplastics, in 2010 we first reported algal photosynthesis impaired by the surface adsorption of cationic and anionic polystyrene (PS) nanoparticles. [19] Later studies have revealed that nanoplastic accumulation in the gonad of Caenorhabditis elegans hampered their reproductivity and energy metabolism, [20] while gestational exposure to high-dose nanoplastics incited hepatic steatosis in the dam and dysregulation of de novo lipogenesis in mice.…”
Section: Introductionmentioning
confidence: 99%